Using biological traits and environmental variables to characterize two Arctic epibenthic invertebrate communities in and adjacent to Barrow Canyon. (June 2018) - Rand, Kimberly; Logerwell, Elizabeth; Bluhm, Bodil; Chenelot, Héloïse; Danielson, Seth; Iken, Katrin; Sousa, Leandra
Abstract: The Arctic's Barrow Canyon, located in the northeastern Chukchi and western Beaufort seas, supports a rich and diverse benthic ecosystem and is often termed an ecological "hotspot" of productivity. Within and adjacent to Barrow Canyon, the epibenthic invertebrate communities vary, with biomass and taxonomic distributions related to habitat variation. Here we asked if the patterns observed are due to Barrow Canyon's variation in near-seafloor physical hydrography, and whether differences in taxonomic distribution also reflect differences in functional properties of the epibenthic invertebrate community. Data were collected using a standardized 83–112 bottom trawl during two surveys in and adjacent to Barrow Canyon: the northeast Chukchi Sea survey in 2013 and the western Beaufort Sea survey in 2008. A portion of the Beaufort Sea survey also used a liner to retain smaller organisms. A suite of nine environmental variables were examined, that included depth, bottom water temperature, bottom hardness as measured by acoustics, and circulation model hindcast current speed. They explained 18–47% of observed variance for each of the three data sets (Chukchi Sea, Beaufort Sea lined net (LN), Beaufort Sea unlined net (UN)). In the Chukchi Sea, bottom hardness and depth were significant variables. In the Beaufort Sea LN hauls, depth, bottom temperature, and the mean current speed on the day of sampling were significant variables and in the Beaufort Sea UN hauls, depth was the only significant variable. Of the 150+ collected taxa from each survey, 20 made up 90% of the total biomass in the Beaufort and Chukchi Seas, and six of the 20 taxa were common to both study areas. We used biological traits analysis (BTA) of body morphology, trophic, and reproductive traits to further characterize the epibenthos at the head of Barrow Canyon in the Chukchi Sea and into Barrow Canyon in the Beaufort Sea. Although the Chukchi and Beaufort seas differed taxonomically in abundance and distribution, they were functionally similar based on the biological traits we examined. A traits analysis can advance knowledge of a community of organisms; however, it is most informative if used as a complement to a taxonomic composition analysis of abundance and distribution.